Pengaruh Return on Assets (ROA), Net Profit Margin (NPM), dan Debt to Equity Ratio (DER) terhadap Nilai Perusahaan Sektor Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2018–2022 - Ipit, Hayati - (Jurnal KIAFE, 2024)
This study examines the effects of Return on Assets, Net Profit Margin, and Debt-to-Equity Ratio on firm value in coal-mining companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data obtained from annual financial statements and stock-price information. The sample was selected through purposive sampling and consisted of 11 companies, resulting in 55 firm-year observations. Firm value was measured using the market-to-book value ratio. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 26. The results show that Return on Assets has a positive and significant effect on firm value, while Net Profit Margin has a negative and significant effect. Debt-to-Equity Ratio has no significant effect on firm value. Simultaneously, Return on Assets, Net Profit Margin, and Debt-to-Equity Ratio do not significantly affect firm value. The adjusted coefficient of determination is 6.3%, indicating that the three independent variables explain 6.3% of the variation in firm value, while the remaining 93.7% is explained by other factors outside the research model.